2016
DOI: 10.1007/s10140-016-1378-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings in emergency imaging: frequency, recommendations, and compliance with consensus guidelines

Abstract: The purpose of this study was to evaluate the frequency of incidental findings (IFs) in emergency department (ED) imaging reports and evaluate the adherence of imaging recommendations to consensus societal guidelines for IFs. A retrospective review of consecutive ED computed tomography (CT) and ultrasonography (US) reports from two university-affiliated EDs over a 2-month period was performed. Each imaging report was reviewed in its entirety, and incidental findings were documented along with recommendations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…and 43% by Munk et al . Hann et al ., meanwhile, reported detecting incidental findings in 64% of cases in an investigation of emergency outpatient services. With regard to the body region, incidental findings are most commonly recognized in the ovaries, lungs, liver, and kidneys .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…and 43% by Munk et al . Hann et al ., meanwhile, reported detecting incidental findings in 64% of cases in an investigation of emergency outpatient services. With regard to the body region, incidental findings are most commonly recognized in the ovaries, lungs, liver, and kidneys .…”
Section: Discussionmentioning
confidence: 93%
“…Hann et al ., meanwhile, reported detecting incidental findings in 64% of cases in an investigation of emergency outpatient services. With regard to the body region, incidental findings are most commonly recognized in the ovaries, lungs, liver, and kidneys . The frequency is considered higher among patients who undergo whole‐body CT than in those who undergo selective CT .…”
Section: Discussionmentioning
confidence: 99%
“…Advances in cross-sectional imaging have led to the discovery of innumerable incidental liver lesions [2][3][4]. Such lesions will be detected in up to 30% of individuals older than 40 years [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Although most are benign, in many cases, further workup can be difficult to avoid.…”
Section: Nature and Scope Of The Problemmentioning
confidence: 99%
“…Studies have shown that there is significant heterogeneity in radiologist classification of AIFs and characterization of the risk associated with each, and almost a third of recommendations were discordant with societal guidelines. 5 In addition, some patients may not have a PCP, or have a PCP outside of the health system, making it difficult to notify a PCP of the finding. Furthermore, for patients who are in the ED or in the hospital as an inpatient, they may have much more pressing health issues which overshadow an AIF detected on imaging during their stay.…”
Section: The Current Approachmentioning
confidence: 99%